La invención del arte colonial en la era del progreso: crítica, exposiciones y esfera pública en Quito durante la segunda mitad del siglo XIX (Dossier: Historias críticas del arte; diálogos transdisciplinarios e indagaciones sobre la estructuración del campo artístico) - Fernández Salvador, Carmen (2018)
This research provides an account of the selection process whereby colonial art in nineteenth-century Ecuador is perceived. To this end, the appearance of a sort of budding art criticism is highlighted, one that is concerned about educating the modern observer. It also examines how the country’s artistic canon was being tentatively shaped. In this framework, the liberals can be seen promoting a democratic society, whereas the views of conservatives were expressed by the contributions made by the thinker Juan León Mera.